Bilateral ovarian malignant mixed Mullerian tumour: a rare entity. (29th August 2013) - Kumar, Madhu; Goel, Madhu Mati; Das, Vinita
Abstract : A 52-year-old postmenopausal woman presented with abdominal distension for 2 months. She had no vaginal bleeding and no relevant medical history. A physical examination showed a large palpable pelvic mass. A CT scan showed an ill-defined, heterogeneously enhancing, soft tissue attenuation lesion in the lower abdomen and pelvis involving the right adnexal region with massive ascites, and the left ovary did not reveal any evidence of disease. The omentum was thickened and heterogeneous. The patient underwent a total hysterectomy with infracolic omentectomy. The diagnosis was bilateral ovarian malignant mixed Mullerian tumour (MMMT) with omental deposits. Aggressive treatment includes surgery and chemotherapy. Women with this tumour have a significant increased risk of death compared to women with epithelial ovarian cancer and very poor prognosis. We report a case of MMMT of the ovary with clinicopathological correlation and diagnostic difficulties as malignant epithelial tumour resemble ovarian stromal sarcoma in postmenopausal female.